Exploring Student and Advisor Experiences in a College-University Pathway Program: A Study of the Bachelor of Commerce Pathway - Percival, Jennifer; Goodman, Bill; LeSage, Ann; Longo, Fabiola; DiGiuseppe, Maurice; De La Rocha, Arlene; Samis, John; Hinch, Ron; Sanchez, Otto (Canadian Journal of Higher Education, 2015)
Currently, there is great interest across Ontario in the expansion of pathway programs between colleges and universities. Through strategic partnerships, two Ontario-based postsecondary institutions (a college and a university) have developed innovative and effective pathway programs that facilitate the transition of students between institutions for the completion of degrees, diplomas, and certificates. These programs support the training of highly qualified, market-ready graduates. This paper reports on a mixed-methods study of the successes and challenges of a particular Ontario college and university pathway program, with a focus on the Bachelor of Commerce Pathway program. Preliminary results indicate that pathway students were more academically successful than their traditional university student counterparts but did experience a number of challenges in transitioning from college into university. Principal challenges included inefficient communication between program administrators, academic advisors, and students; lack of orientation activities for pathway students; lack of college student preparedness in communication and critical thinking skills; and difficulties experienced by college students integrating into the social-cultural life of the university.